Energy Efficient Approach Through Intelligent Transportation System: A Review - Chai, N.P; W. A. W. Z., Abidin; W. H. W., Ibrahim; K., Hong Ping (ENCON 2013, 2013)
In many countries, the number of vehicles increases every year but insufficient transportation infrastructure is causing great impact on transportation sustainability. The challenges in public sustainable access and mobility reduce the energy efficiency in transportation system. Moreover, the reduction of unsustainable energy resources such as coal, petroleum, and natural gases has receiving more attention from policy makers, academia, industry and public. In order to realize sustainable transportation, Intelligent Transportation System (ITS) is proposed and implemented respectively in many countries. ITS is a state-of-the-art approach which amalgamates surveillance, communication and information technologies to improve sustainability of transportation. This paper presents a review on progress and development of ITS in selected countries. The studies show that the applications of ITS does provide better energy efficiency in transportation system.